AB0433 Prevalence of osteopenia and osteoporosis in women with systemic lupus erythematosus. (23rd January 2014) - Salman Monte, T. C.; Pérez Ruiz, J.; Torrente-Segarra, V.; Mojal, S.; Padró, I.; Carbonell, J.
Abstract : Background: Systemic Lupus Erythematosus (SLE) is a chronic, autoimmune disease characterized by acute and chronic inflammation of various tissues of the body. Studies have found an increase in bone loss and fracture in individuals with SLE compared to general population (1 ). Objectives: The aim of this study was to describe the prevalence of osteopenia - osteoporosis and to find possible predictors of bone loss in our cohort of patients with SLE. Methods: Retrospective, descriptive study of patients with SLE (ACR 1982 revised criteria) who were referred for bone densitometry in the Department of Rheumatology at the Parc de Salut MAR (Barcelona, Spain) between June of 2007 and January 2010. For each patient demographic and clinical information was collected as well as the results of the densitometry measured in g/cm 2 . The normal values for Hologic QDR 4.500 SRY super tm Bone Densitometer are shown in Table 1 . Results: The prevalence of osteopenia – osteoporosis in our cohort is presented in Table 2. From a total of 105 SLE patients, 102 were women. We collected 67 bone density measurements of female SLE patients. Of the 67 patients, 55 (82.0%) were Caucasians, 7 (10.4%) patients of Asian ethnicity and 5 (7.4%) South American. 47 were smokers (70.1%). 54 were treated with azathioprine (80.5%), 45 (67.1%) used corticosteroids and 19 (28.3%) received steroid bolus (defined as at least 3 months of treatment with prednisone 1mg/kg until the densitometric study was made). 42 (62.6%) patients had been taking vitamin D, 25 (37.3%) calcium supplements and 26 (38.8%) patients received bisphosphonate therapy. 47 (70.1%) patients used sun blockers. The mean age was 53.2 ± 16.8 years, the mean weight was 64.6 ± 11.8 kg and the mean height was160.2 ± 5.9 cm. The mean lumbar bone mineral density (BMD) was 0.96 ± 0.12 g/cm 2, the mean hip BMD was 0.87 ± 0.13 g/cm 2 and the mean femoral neck BMD was 0.76 ± 0.12 g/cm 2 . The mean MHAQ was 0.39 ± 0.65, the mean visual pain analog scale (VAS) was 37.1 ± 29.5, the mean SLEDAI was 0.99 ± 1.87, the mean SLICC 0.58 ± 0.83, the mean ANA serum concentration was 1401.7 ± 1808.7 the mean Anti-dsDNAserum concentration was 169.8 ± 386.5 UI/ml, the mean ESR was 21.2 ± 16.1 mm/h, the mean CRP was 0.8 ± 3.6 mg/dl, the mean C3 was 110.1 ± 25.1 mg/dl, mean C4 20.4 ± 11.1 mg/dl, mean PTH 53.1 ± 25. 0 pg/ml and mean serum concentration of 25 OH vitamin D was 23.3 ± 15.5 ng/ml. The only statistically significant correlation was found was between weight and height (body mass index, BMI) and hip and neck BMD (Table 3). Conclusions: We found no predictors of bone loss in relation to the disease activity or its treatment, including the use of corticosteroids. The only significant correlation was a positive relationship between BMI and BMD which is in agreement with data found in general population and in other series of patients with SLE (2 ). References: Yee CS et al. Prevalence and predictors of fragility fractures in systemic lupus erythematosus. Ann Rheum Dis 2005;64:111–4. Irene E. M. Bultink et al. Prevalence of and Risk Factors for Low Bone Mineral Density and Vertebral Fractures in Patients With Systemic Lupus Erythematosus. Arthritis Rheum. 2006;54:378-9. Disclosure of Interest: None Declared